Assessment of Ecosystem Characteristics and Fishery Carbon Sink Potential of Qianxiahu Reservoir Based on Trophic Level and Carbon Content Methods - Mei Liu; Mengxia Shu; Qingping Lian; Aihuan Guo; Dan Zhou; Songbao Zou; Julin Yuan; Guangmei Chen (Fishes)
Optimizing biological carbon sequestration has become a primary strategy in global low-carbon-emission initiatives. Freshwater fisheries in reservoirs play an important role in aquatic biological carbon sequestration. However, a standard method for evaluating the carbon sink capacity of inland fisheries has not been developed. Therefore, this study aimed to assess and compare the carbon sequestration potential of the Qianxiahu Reservoir’s fisheries using the trophic level and mass-balance methodologies. The Ecopath model was employed to determine the trophic levels of aquatic organisms within the Qianxiahu Reservoir ecosystem, with input parameters sourced from in situ surveys and the literature on reservoirs. The model includes 21 functional groups, with trophic levels ranging from 1.000 to 3.281. The key species identified are silver carp, bighead carp, and crucian carp. The indices of Finn’s cycling index (FCI), connectivity index (CI), system omnivory index (SOI), and total primary production/total respiration (TPP/TR) for the Qianxiahu Reservoir are 11.35, 0.27, 0.196, and 1.540, respectively. These values indicate a high degree of material recycling and complex interconnections among functional groups. The fishery carbon sink potential of the Qianxiahu Reservoir, calculated using the trophic level and carbon content methods, yielded values of 261.8362 tons/km2 and 66.6818 tons/km2, respectively. The trophic level method showed a notable increase of 195,1544 tons/km2 compared to the carbon content method, underscoring significant differences in results between the two methods. The study concludes with recommendations for research on methods to assess the carbon sink capacity of freshwater fisheries, aiming to establish a scientific framework for this evaluation.